The Effect of Leadership Style on Employee Satisfaction - Suhardjono, Callista; Djumardi, Caroline Calista; Djovanka, Djovanka; Tannescia, Jeslyn Michelle; Juliana, Juliana (Jurnal EMT KITA, 2026)
This study aims to analyze the effect of leadership style on employee satisfaction in the hospitality industry. A quantitative method was employed by distributing questionnaires to 101 hotel employees across Indonesia using convenience sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results revealed that leadership style has a positive and significant effect on employee satisfaction, with an R-squared value of 0.591 and a path coefficient of 0.769 (p-value = 0.000). These findings highlight the importance of adopting effective leadership approaches to enhance employee psychological well-being and job satisfaction. This study provides practical recommendations for hotel management to design HR strategies that promote participative and transformational leadership.